Impact of overconfidence among finance managers on forecasted market returns: Evidence from India. Issue 2 (9th September 2020) - Mundi, Hardeep Singh; Nagpal, Era
Abstract : The current article studies the impact of overconfidence among finance managers on forecasted market returns in India. Overconfidence among finance managers is measured using a standardised questionnaire and data is collected from February, 2017 to October, 2018. Snowball sampling is used as the sampling technique to collect data from 200 finance managers. The secondary data for the study is collected from the Centre for Monitoring Indian Economy (CMIE) Prowess. Overconfidence among finance managers is modelled as per the methodology of Ben‐David, et al. (2013). After running a regression model to test whether overconfidence among finance managers results in more accurate forecasts of market returns, it is found that overconfident finance managers predict forecasted error with more accuracy and also predict narrow confidence intervals. Fama and MacBeth regression results present that finance managers are overconfident after their decisions of forecasted market returns are accurate. Overconfidence among managers is not due to the skill of managers but is present because overconfident managers are often miscalibrated. Key words: Behavioural corporate finance, bias of overconfidence, decision‐making, forecasted market returns.